On the issue of efficiency of demonstrating a physics experiment at school - Jakutis, S.; Valentinavičius, V. (Psichologija, 1962)
When improving the content and methods of the school course used when teaching physics, it is necessary to develop demonstration experiment. It is expedient to abandon a special schematic illustration of devices. Their structure must meet the equipment used in practice to a particular extent. A demonstration experiment must also reflect the newest achievement in technology.The demonstration experiment must be used not only for teaching new material, but also in other stages of a lesson. The involvement of students into preparation for the demonstration experiment and conduction thereof has a positive effect on the quality of their knowledge, as well as the development of practical faculties and skills.
Keywords: demonstration experiment and teaching of physics